Edukasi Cara Merawat Orang dengan HIV/AIDS pada Caregiver di Kabupaten Tanah Karo: Educating Tanah Karo District Caregivers on How to Take Care for Individuals with HIV/AIDS - Sihombing, Yulia; Theresia, Theresia; Sinulingga, Elysabeth; Sampepadang, Mega; Debby, Chryest (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
People living with HIV/AIDS (PLWHA) often experience stigma and discrimination in the community, so they usually keep their HIV/AIDS status a secret and experience rejection by both family and the community. An informal caregiver is a companion, consisting of friends, neighbors, or volunteers, who take care of PLWA who are excluded by their family and need help/assistance to carry out activities related to daily needs and medication. The Commission for HIV/AIDS and Drug Control (KPA) GBKP Moderamen Tanah Karo shelters and assists volunteers who act as caregivers of PLWHA. The purpose of this PKM is to provide health education related to PLWHA assistance, aiming to increase caregiver capacity and enrich the knowledge of KPA GBKP staff. The method of conducting PKM is by educating caregivers on how to care for people living with HIV/AIDS through online seminars delivered by PKM team members. The results of this PKM showed an increase in knowledge, as indicated by a rise in the pretest mean from 66.8 to 80.5 in the posttest. Health education increases caregiver knowledge, as evidenced by the posttest average, which shows a significant increase in knowledge.